Efficacy of Erenumab in the Treatment of Trigeminal Neuralgia: A Retrospective Case Series. Issue 3 (June 2021) - Parascandolo, Eliot; Levinson, Kelsey; Rizzoli, Paul; Sharon, Roni
Abstract : Objective: Trigeminal neuralgia (TN) is a chronic, often refractory, pain condition, which adversely affects the lives of patients. Current treatments are only mildly effective. Anti–calcitonin gene-related peptide (CGRP) monoclonal antibodies have been successfully studied in the treatment of migraines. CGRP plays a role in both TN and migraine. It is prudent to attempt CGRP monoclonal antibody therapy in TN. Erenumab, a human anti-CGRP monoclonal antibody medication, modulates CGRP, which is elevated in patients with TN. The primary objective of this study was to evaluate the efficacy of erenumab for patients with TN. Methods: Retrospective analysis was performed on data collected from 10 patients diagnosed with TN and treated with erenumab for 6 months. Pain was tracked using a numeric pain rating scale (NPRS) from 0 to 10. The effect of erenumab on NPRS after 6 months' time was the primary end point. Secondary end points included side effects to therapy, improvement in headache frequency in those with comorbid migraine, evaluating mood following therapy, and global mood improvement using scale (worse, no change, improved). Results: Nine of 10 patients (90.0%) reported improvement in pain severity and in global mood improvement. Three patients reported resolution of anxiety and/or depression. Side effects were minimal, with 3 patients reporting constipation, injection site reactions, or both. Conclusions: Based on these results, erenumab appears to be an efficacious treatment option for patients with refractory TN. Patients experienced improvement in pain, reduced frequency of headache, and improvement in mood. Treatment was well tolerated with only mild side effects reported. Classification of Evidence: This study provides Class IV evidence that erenumab increases the probability of improved pain control in patients with medication-resistant TN.